International Hip Outcome Tool (12-items) as health-related quality-of-life measure in osteoarthritis: validation of Greek version - Sophia Stasi; Magdalini Stamou; George Papathanasiou; Paraskevi Frantzeskaki; Emmanouil Kanavas; George Evaggelou-Sossidis; Adamantios Gouskos; Andreas Palantzas; Kyriakos Poursanidis; George A. Macheras (SpringerOpen, 2020)
Abstract Background The 12-item International Hip Outcome Tool (iHOT12) is a patient-reported outcome (PRO) designed to evaluate quality of life. We assessed the psychometric properties of the Greek version (iHOT12-Gr) in hip osteoarthritic patients. Methods Data from 124 patients aged > 50 years were used for factor analysis. Reliability evaluation included internal consistency, test-retest reliability, and interpretability. Content validity was examined by calculating the item-level content validity indices (I-CVI) and the scale-level content validity indices (S-CVI), using two methods: S-CVI Average (S-CVI/Ave), and the S-CVI Universal Agreement among experts (S-CVI/UA). Construct validity was tested against Greek versions of the Lower Extremity Functional Scale (LEFS-Greek), Modified Harris Hip Score (MHHS-Gr), and the 30 s chair-to-stand, Timed Up & Go (TUG), and 9-stairs-ascend/descend (9S-A/D) tests. Known-groups validity was examined using LEFS-Greek (cut-off = 53 points) as estimate variable. Responsiveness was examined pre and post total hip arthroplasty (4 and 8 weeks). Results Factor analysis revealed a two-factor model. Factor-1 (items 1-9) reflects "Symptoms and functionality", while Factor-2 (items 10-12) reflects "Hip disorder-related concerns". Reliability: Internal consistency and test-retest reliability of iHOT12-Gr-total were excellent: Cronbach's alpha > 0.92 and ICC(95% CI) > 0.976(0.96-0.99)(p < 0.001). Interpretability: There was no floor or ceiling effect; measurement error: 3.72 (Factor-1), 3.64 (Factor-2), and 3.22 (iHOT12-Gr-total); minimal detectable change: 10.3 (Factor-1), 10.1 (Factor-2), and 8.92 (iHOT12-Gr-total). Validity: Content validity: The I-CVI value of the 12 items ranged from 1.00 to 0.83, the S-CVI/Ave was 0.97 and the S-CVI/UA was 0.83. Construct validity: iHOT12-Gr correlated strongly with both LEFS-Greek and MHHS-Gr, and weakly but significantly with 30s chair-to-stand, TUG and 9S-A/D (p < 0.001). Known-groups validity showed that iHOT12-Gr well discriminated subgroups of patients (p < 0.001). ROC analysis cut-off points were 51.9 (Factor-1), 25 (Factor-2) and 45.2 (iHOT12-Gr-total) (p < 0.001). Responsiveness: Four and 8 weeks postoperatively, standardized response means of Factor-1, Factor-2, and iHOT12-Gr-total were > 0.8. Conclusion iHOT12-Gr showed excellent reliability properties. The content validity was excellent and significant weak-to-strong correlations were found regarding construct validity. The known-group validity was also significant, while the responsiveness was excellent. iHOT12-Gr could be a reliable and valid PRO for assessing quality of life in patients with hip osteoarthritis.